2017
DOI: 10.1186/s12978-017-0323-4
|View full text |Cite
|
Sign up to set email alerts
|

Respectful maternity care in Ethiopian public health facilities

Abstract: BackgroundDisrespect and abuse of women during institutional childbirth services is one of the deterrents to utilization of maternity care services in Ethiopia and other low- and middle-income countries. This paper describes the prevalence of respectful maternity care (RMC) and mistreatment of women in hospitals and health centers, and identifies factors associated with occurrence of RMC and mistreatment of women during institutional labor and childbirth services.MethodsThis study had a cross sectional study d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
125
10
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(165 citation statements)
references
References 31 publications
22
125
10
4
Order By: Relevance
“…The odds of RMC were two times higher among women whose labor attended by male providers. This finding is in line with the study conducted at public hospitals of Ethiopia in which, male HCPs were more likely to engage in the implementation of RMC [25]. This is challenging to explain but it might be due to the natural inclination to opposite-sex rather than the quality of care provided.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The odds of RMC were two times higher among women whose labor attended by male providers. This finding is in line with the study conducted at public hospitals of Ethiopia in which, male HCPs were more likely to engage in the implementation of RMC [25]. This is challenging to explain but it might be due to the natural inclination to opposite-sex rather than the quality of care provided.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, merely 38.4% of women received RMC. This finding is higher than the study conducted in Addis Ababa (21%) [7] and lower than the studies conducted in public hospitals of Ethiopia (66%), Bahir Dar, Ethiopia (57%), Uttar Pradesh, India (43%), Tanzania (85%), and Kenya (80%) [22,24,25,33,34]. This incongruity may be due to study period variation, participant's level of understanding about the service, educational and socio-economic status of the participants, service quality, and the ability of participants to report D&A.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This could well be due to routine performance evaluations that were implemented in health services at the time of this study. Another reason was that the majority of the health institutions in the study also allowed women, but not men, to accompany women in the labour ward [21,23]. …”
Section: Discussionmentioning
confidence: 99%
“…The most frequently mentioned form of disrespect and abuse in the open-ended comments was abandonment and neglect". Another study by Sheferaw et al [4] found that women on average received 5.9 (66%) of the nine recommended RMC practices. Health centres demonstrated higher RMC performance than hospitals.…”
Section: Introductionmentioning
confidence: 98%